Pengembangan Media Pembelajaran Berupa Buletin dalam Bentuk Buku Saku untuk Pembelajran IPA Terpadu - Asyhari, Ardian; Silvia, Helda (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2016)
This research aims to; 1) develop learning media in the form of an integrated science bulletin on sound material; 2) investigate the response of students to the feasibility study media in the form of an integrated science bulletin on sound material for students of class VIII, with the formulation of the problem; 1) How to develop learning media in the form of an integrated science bulletin on sound material ?; 2) How is the response of students to the feasibility study media in the form of an integrated science bulletin on sound material. This study is a R & D method which adopting development of Borg & Gall. Subjects in this study were students of class VIII SMP Negeri 7 Bandar Lampung and SMPN 21 Bandar Lampung amounted to 40 learners and data collection instruments used in the form of a questionnaire given to subject matter experts, media experts, and a science teacher SMP to test the feasibility of media learning in a bulletin in the form of a pocket book for integrated science teaching. The type of data that is generated is a qualitative and quantitative data were analyzed with the guidelines criteria to determine eligibility assessment category product. The results of this study are; 1) has developed learning media in the form of an integrated science bulletin in the form of a pocket book; 2) feasibility study media bulletin integrated science that has been developed is very feasible with a percentage of 82% is based on an expert assessment materials after the final stage of repair, design expert with a percentage of 79.4% with the criteria of decent; 3) the percentage was 77.6%, a teacher the criterion is a decent; 4) the results of the response of learners with a percentage of 80% with the criteria are eligible.Penelitian ini bertujuan untuk; 1) mengembangkan media pembelajaran berupa buletin IPA terpadu dalam bentuk buku saku pada materi bunyi; 2) mengetahui respon peserta didik terhadap kelayakan media pembelajaran berupa buletin IPA terpadu pada materi bunyi dalam bentuk buku saku untuk peserta didik kelas VIII, dengan rumusan masalah; 1) Bagaimana mengembangkan media pembelajaran berupa buletin IPA terpadu dalam bentuk buku saku pada materi bunyi?; 2) Bagaimana respon peserta didik terhadap kelayakan media pembelajaran berupa buletin IPA terpadu dalam bentuk buku saku pada materi bunyi. Penelitian ini merupakan penelitian R&D yang mengadopsi pengembangan dari Borg & Gall. Subjek dalam penelitian ini adalah peserta didik kelas VIII SMP Negeri 7 Bandar lampung dan SMP Negeri 21 Bandar Lampung berjumlah 40 orang peserta didik dan instrumen pengumpulan data yang digunakan berupa angket yang diberikan kepada ahli materi, ahli media, dan guru IPA SMP untuk menguji kelayakan media pembelajaran berupa buletin dalam bentuk buku saku untuk pembelajaran IPA terpadu. Jenis data yang dihasilkan adalah data kualitatif dan kuantitatif yang dianalisis dengan pedoman kriteria kategori penilaian untuk menentukan kelayakan produk. Hasil penelitian ini adalah; 1) telah dikembangkan media pembelajaran berupa buletin IPA terpadu dalam bentuk buku saku; 2) kelayakan media pembelajaran buletin IPA terpadu dalam bentuk buku saku yang telah dikembangkan adalah sangat layak dengan persentase 82 % berdasarkan penilaian ahli materi tahap akhir setelah perbaikan, ahli desain dengan persentase 79,4% dengan kriteria layak 3) dengan persentase adalah 77,6%, penilaian guru dengan kriteria adalah layak 4) hasil respon peserta didik dengan persentase 80% dengan kriteria layak.